(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2019)
This work deals with political and economic phenomena that express changes and permanence in the agrarian structure, centered on uses and livestock systems. Changes that led to usurpatory acts of community heritage with incidence in the forms of transition, compromising the peasant organization. It analyzes the contradictions that customary practices cross with the advance of agrarian individualism, redefined under the impact of feudalization. It covers processes of the thirteenth and fourteenth centuries in the territories of Castile with an emphasis on private property rights over land and legal conflicts that reflect the dissolution of the allodium and its implications on feudal income. He appeals to the contributions of Marx and Weber to investigate market factors and coercive instruments, analyzing the role of the centralized State in long-term socioeconomic dynamics.